Advances in Quantitative Imaging of Genetic and Acquired Myopathies: Clinical Applications and Perspectives - Paoletti, Matteo; Pichiecchio, Anna; Cotti Piccinelli, Stefano; Tasca, Giorgio; Berardinelli, Angela L.; Padovani, Alessandro; Filosto, Massimiliano (Frontiers in Neurology, 2019)
In the last years, magnetic resonance imaging has become fundamental for the diagnosis and monitoring of myopathies given its ability to show the severity and distribution of pathology, to identify specific patterns of damage distribution and to properly interpret a number of genetic variants. The advances in MR techniques and post-processing software solutions have greatly expanded the potential to assess pathological changes in muscle diseases, and more specifically of myopathies; a number of features can be studied and quantified, ranging from composition, architecture, mechanical properties, perfusion and function, leading to what is known as quantitative MRI (qMRI). Such techniques can effectively provide a variety of information beyond what can be seen and assessed by conventional MR imaging; their development and application in clinical practice can play an important role in the diagnostic process and in assessing disease course and treatment response. In this review, we briefly discuss the current role of muscle MRI in diagnosing muscle diseases and describe in detail the potential and perspectives of the application of advanced quantitative MRI techniques in this field.